Middle kingdom and empire of the rising sun : Sino-Japanese relations, past and present - Dreyer, June Teufel, 1939- (Oxford University Press, 2016)
June Teufel Dreyer's historical synthesis of China and Japan's relationship, Middle Kingdom and Empire of the Rising Sun, provides a jargon-free, concise, and readily understandable overview of one of the world's great civilizational rivalries.